Role of procalcitonin and C-reactive protein in urinary tract infection diagnosis in adults - M. S., Bharath; Hiremath, Ramesh S.; Basu, Arini (International Journal of Advances in Medicine, 2017)
Background: Urinary tract infections are a common group of infections encountered in adults, and their treatment and prognosis are closely correlated with the location of infection. Clinical presentation and laboratory tests are insufficient to differentiate between upper urinary tract infection and lower urinary tract infection. So this study was conducted to explore a non-invasive diagnostic method for upper and lower urinary tract infection differentiation. Methods: A case-control study included 2 groups of patients –30 cases and 30 controls. Cases further classified into 2 groups- a) Patients having upper urinary tract infection; b) Patients having lower urinary tract infection. Patients were subjected to following tests – complete hemogram, blood C-reactive protein levels, serum procalcitonin levels, urinalysis, ultrasound abdomen. Results: Procalcitonin (PCT) and CRP values with upper urinary tract infection were significantly higher than those in with lower urinary tract infection. PCT has higher -sensitivity and a specificity than CRP. Conclusions: Both procalcitonin and CRP can be used for upper and lower urinary tract infection differentiation, but Procalcitonin has higher sensitivity and specificity in predicting Upper urinary tract infection than CRP.